2016
DOI: 10.19082/1966
|View full text |Cite
|
Sign up to set email alerts
|

ssociation between serum visfatin and carotid atherosclerosis in diabetic and non-diabetic patients on maintenance hemodialysis

Abstract: IntroductionAdipose tissue releases bioactive factors termed adipokines. Visfatin is an adipokine that plays an active role promoting vascular inflammation and atherosclerosis. The purpose of this study was to determine the association between serum visfatin levels and carotid atherosclerosis in diabetic and non-diabetic patients on maintenance hemodialysis (HD) in order to clarify the role of serum visfatinas, a risk factor for cardiovascular complications in HD patients.MethodsForty patients on maintenance h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that oxidative stress is one of the key factors responsibl e for liver damage and brain ageing via oxidative injury, as revealed by the over-production of the lipid peroxidation marker MDA and the increasing antioxidant activities of CAT, GSH-Px, SOD, and T-AOC. SOD is the first gatekeeper in the antioxidant defence system by catalysing the dismutation of the superoxide anion to oxygen and hydrogen peroxide (H 2 O 2 ), the latter of which is further metabolized by CAT or GSH-Px 43 45 . T-AOC is representative of all antioxidants, and MDA is well-recognized not only as an indicator of ageing but also as the most important product of membrane lipid peroxidation, and thus, it indirectly reflects the level of cell oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that oxidative stress is one of the key factors responsibl e for liver damage and brain ageing via oxidative injury, as revealed by the over-production of the lipid peroxidation marker MDA and the increasing antioxidant activities of CAT, GSH-Px, SOD, and T-AOC. SOD is the first gatekeeper in the antioxidant defence system by catalysing the dismutation of the superoxide anion to oxygen and hydrogen peroxide (H 2 O 2 ), the latter of which is further metabolized by CAT or GSH-Px 43 45 . T-AOC is representative of all antioxidants, and MDA is well-recognized not only as an indicator of ageing but also as the most important product of membrane lipid peroxidation, and thus, it indirectly reflects the level of cell oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Under different conditions including metabolic syndrome, type 2 DM, rheumatic disease, and hemodialysis, visfatin had a positive correlation with the presence and severity of the disease [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…*p < 0.05 vs respective basal values in the absence of visfatin/eNampt. Indeed, the link between visfatin/eNampt and cardiovascular diseases has been even reinforced by more recent reports 28,29 , both in the presence or in the absence or metabolic alterations 19,30,31 . A common ground of clinical studies linking visfatin/eNampt with cardiovascular diseases highlights the clear relationship between this adipokine and a pro-inflammatory context [32][33][34] .…”
Section: Figurementioning
confidence: 95%